Produtividade da alface americana submetida a diferentes lâminas de irrigação - Lima Jr., Joaquim Alves de; Pereira, Geraldo Magela; Geisenhoff, Luciano Oliveira; Boas, Renato Carvalho Vilas; Silva, Wellington Gomes da; Silva, Andre Luiz Pereira da [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
With the aim of minimizing the difficulties faced by the producers on cultivating the crisphead lettuce (Lactuta sativa L), specifically those related to the lack of technical information about the quantity of water to be applied, a study was made in order to determine the effect of various water depths on crisphead lettuce yielding characteristics. The experiment was carried out at the Universidade Federal de Lavras (UFLA), from October to December 2008 in greenhouse. A randomized block design with five treatments and four repetitions was applied. The treatments, consisting of the five respective evaporation factors; , 0.30 EVm; 0.60 EVm; 0.90 EVm; 1.20 EVm; 1.50 EVm (evaporate depth), were done according to an evaporated depth of a reduced pan. The results showed that: The maximum commercial yield, 36.5 t ha(-1), was estimated by applying a 164.8 mm depth, which corresponded to a water reposition factor of 98 %; the highest water usage efficiency (962.45 kg ha(-1) mm(-1)) was attained when an irrigation depth of 50.10 mm (30%) was used.
Yield of crisphead lettuce under different amounts of irrigation
Keywords: Greenhouse; Irrigation depths; Lactuta sativa L.